Answer:
4k + 2j + 1
Step-by-step explanation:
5k + 3 + 2j – 2 – k =
5k - k + 2j + 3 - 2
4k + 2j + 1
4,120 pounds ← error = 6 lbs
<span>4,100 pounds ← error = 26 lbs </span>
<span>4,200.34 pounds ← error = 74.34 lbs </span>
<span>4,500.765 pounds ← error = 374.765 lbs</span>
Answer: There is one valid solution to the equation 5x + 8 - 7x = -4x + 1, x = -3.5.
Step-by-step explanation:
Answer:
26042.
Step-by-step explanation:
What's the first term of this geometric series?
2.
What's the common ratio of this geometric series?
Divide one of the terms with the previous term. For example, divide the second term -10 with the first term 2.
.
What's the sum of this series to the seventh term?
The sum of the first n terms of a geometric series is:
,
where
is the first term of the series,
is the common ratio of the series, and
is the number of terms in this series.
.
Answer:
x=12
Step-by-step explanation:
16x-30-(14x-6)=2x-24=0. add 24 on both sides to get 2x=24. divide by 2 on both sides to get x=12